Application of cell sheet technology to bone marrow stromal cell transplantation for rat brain infarct. (12th June 2014) - Ito, Masaki; Shichinohe, Hideo; Houkin, Kiyohiro; Kuroda, Satoshi
Abstract: Bone marrow stromal cells (BMSC) transplantation enhances functional recovery after cerebral infarct, but the optimal delivery route is undetermined. This study was aimed to assess whether a novel cell‐sheet technology non‐invasively serves therapeutic benefits to ischemic stroke. First, the monolayered cell sheet was engineered by culturing rat BMSCs on a temperature‐responsive dish. The cell sheet was analysed histologically and then transplanted onto the ipsilateral neocortex of rats subjected to permanent middle cerebral artery occlusion at 7 days after the insult. Their behaviours and histology were compared with those in the animals treated with direct injection of BMSCs or vehicle over 4 weeks post‐transplantation. The cell sheet was 27.9 ± 8.0 μm thick and was composed of 9.8 ± 2.4 × 10 5 cells. Cell sheet transplantation significantly improved motor function when compared with the vehicle‐injected animals. Histological analysis revealed that the BMSCs were densely distributed to the neocortex adjacent to the cerebral infarct and expressed neuronal phenotype in the cell sheet‐transplanted animals. These findings were almost equal to those for the animals treated with direct BMSC injection. The attachment of the BMSC sheet to the brain surface did not induce reactive astrocytes in the adjacent neocortex, although direct injection of BMSCs profoundly induced reactive astrocytes around the injection site. These findings suggest that the BMSCs in cell sheets preserve their biological capacity of migration and neural differentiation. Cell‐sheet technology may enhance functional recovery after ischaemic stroke, using a less invasive method. Copyright © 2014 John Wiley & Sons, Ltd.